The role of the microtubule manufacturing chaperone TBCD in neuronal development and brain disorders - Rowlands, Jordan Gareth David (Curtin University, 2021)
Tubulin-specific chaperone D is a microtubule manufacturing chaperone essential to the ability for cells to adopt their appropriate shape, to undergo cell division, as well as to maintain metabolic homeostasis. Recently, homozygous missense mutations to the TBCD gene were reported to cause a severe, early onset neurodegenerative condition in infants. This thesis illuminates the vast and interconnected molecular mechanisms through which TBCD and its clinically-relevant mutations influence cell cycle, metabolism and differentiation.